The backpacker tourist : a contemporary perspective - Martins, Márcio Ribeiro; Costa, Rui Augusto da (The tourist experience, 2022)
Previously viewed as a relatively small group of errant travellers rooted in counter-cultural ideas, backpackers have now become a powerful tourist sector of predominantly young travellers, planning and preparing their own trips, and looking for direct cultural contact, novelty and spontaneity all around the globe. The Backpacker Tourist: A contemporary perspective explores the increasing number of people traveling around the world as backpackers and analyses the great diversification of this demographic and their varied experiences while traveling. Martins and Costa highlight the conflicting interpretations in the literature on backpackers and the comparative reflexion between Western and the growing number of Eastern backpackers, particularly relating to their travel motivations and the way they experience destinations. The Backpacker Tourist presents new perspectives to researchers of Tourism Studies and the Sociology of Travel, but also to those who looking for a synthetical, contemporary and critical analysis of contemporary backpacker tourists.